2012
DOI: 10.1515/sg-2012-0032
|View full text |Cite
|
Sign up to set email alerts
|

Estimating coancestry within open-pollinated progenies of a dioecious species: the case study of Myracrodruon urundeuva

Abstract: Understanding the coancestry coefficient within openpollinated progenies has long been an area of interest because of the implications of coancestry on estimates of additive genetic variation, variance effective size and the number of seed trees required for seed collection for ex situ conservation, tree breeding and environmental restoration. This study compares three methods to calculate the coancestry coefficient within open-pollinated progenies of the dioecious tree species, Myracrodruon urundeuva, using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…But the estimated values were in some cases lower than 0.125, ranging from -0.022 to 0.309. The cause of lower than expected pairwise estimates is the fact that estimates of relatedness based on genetic markers need a large number of loci, ideally about 20 (Moraes et al, 2012;Ritland, 1996;Wang, 2011). The seven loci used here are probably not sufficient for robust estimates of all pairwise coancestry coefficients.…”
Section: Inbreedingmentioning
confidence: 89%
“…But the estimated values were in some cases lower than 0.125, ranging from -0.022 to 0.309. The cause of lower than expected pairwise estimates is the fact that estimates of relatedness based on genetic markers need a large number of loci, ideally about 20 (Moraes et al, 2012;Ritland, 1996;Wang, 2011). The seven loci used here are probably not sufficient for robust estimates of all pairwise coancestry coefficients.…”
Section: Inbreedingmentioning
confidence: 89%
“…As the endogamy originating from mating between related individuals is equal to the coancestry coefficient among parents (Moraes et al, 2012), which in the present case of full-sibs is 0.25, we would expect at least 25 % inbreeding in descendants of crossings between the clones suggested for selection. Inbreeding in Eucalyptus species produces inbreeding depression, resulting in mortality, infertility, among other effects, as has been well documented in the literature (Eldridge and Griffin, 1983;Costa and Silva et al, 2011;Wu et al, 2015;Hedrick et al, 2016).…”
Section: Clone Selectionmentioning
confidence: 71%
“…Estimates of pairwise coancestry between parents and descendants were sometimes lower (juveniles-mother: θ 1 = 0.19; juveniles-father: θ 2 = 0.19; PA: offspring-father, θ 2 = 0.13) and sometimes higher (offspring-mother, PA: θ 1 = 0.42; PF: θ 1 = 0.32; offspring-father in PF, θ 2 = 0.29) than expected (0.25). These results can be explained by the fact that estimates of pairwise relatedness between parents using gene markers and probabilistic methods such as those used here (Loiselle et al, 1995) are subjected to bias, which can result in estimates that are different than expected, especially if the number of loci is lower than 20; in our case, estimates were based on six loci (see, Ackerman et al, 2017;Moraes, Gaino, Moraes, Freitas & Sebbenn, 2012).…”
Section: Pairwise Coancestrymentioning
confidence: 83%
“…Due to this, Moraes et al. () have suggested that coancestry within families must be preferentially estimated by mating system indices, especially to determine the variance effective size within families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation